PATHOMORPHOLOGICAL AND CLINICAL CHARACTERISTICS OF BREAST CANCER IN MEN IN THE REPUBLIC OF UZBEKISTAN - Uktam M. Kurbankulov; Munira X. Norbekova (Scholar Express Journals, 2023)
Oncological diseases remain a pressing problem in the world. In recent years, according to official world medical statistics, the incidence of cancer has been increasing worldwide. According to statistics from the World Health Organization (WHO), “by 2030, there will be 15 million people in the world with dangerous diseases, so the system for predicting early diagnosis, as well as surgical treatment and systemic treatment of oncological diseases has not yet been clarified.” WHO notes an annual increase in breast cancer diagnosed in women, but detection of a similar cancer in men is very rare and accounts for 1% of the total number of detected cases, while this disease accounts for about 0.2. Scientific research on male breast cancer is being conducted all over the world, but there are few of them, in this regard, our research helps fill the gap in the assessment and scientific study of this oncological pathology in men, and there are also unique scientific studies devoted to the early diagnosis and prognosis of male breast cancer . Therefore, the pathomorphological and molecular genetic characteristics of breast cancer in men is one of the most important problems of fundamental medicine and oncology.
Keywords: Breast cancer in men; pathogenetic mechanism; detection in the Republic of Uzbekistan